Pemetaan Tingkat Keparahan Kebakaran Hutan dan Lahan Menggunakan Algoritma Nbr (Normalized Burn Ratio) Pada Citra Sentinel 2 - Hamidah, Zannisa; Kusumawati, Lia; Hijrawadi, Sony Nugratama (Geography Education Study Program, Universitas Kanjuruhan Malang, 2025)
Forest and land fires often occur in the Lamandau Regency area, Central Kalimantan, which causes forest function to no longer be optimal due to forest and land fire disasters which continuously occur every year. This research aims to determine the severity of forest and land fires that occurred in Lamandau Regency in 2021 and 2022. The method used in this research is the Normalized Burned Ratio (NBR). The results of the research include mapping the severity of forest and land fires in 2021-2022 in Lamandau Regency. In 2021, the area affected by forest fires reached 151,750 hectares, 48 hectares in the very severe category, 2,156 hectares in the severe category. There will be a decrease in 2022 with an area affected by forest and land fires of 40,982 hectares, a reduction of more than 50% from 2021. The area of very badly burned areas has decreased, to 0.08 hectares. Meanwhile, the area of severely burned areas experienced a significant decrease, reaching 207 hectares. The land use affected in 2022 is forest of 82,284 hectares, plantations of 53,921 hectares. Other land uses such as open land and settlements do not have a large enough impact with an affected area of 1000 hectares. The worst affected land use in 2022 will be forests covering an area of 27,284 hectares, plantations covering an area of 10,361 hectares. However, in the use of residential land and built-up land as well as open land, the area burned has increased by 1000 hectares. This study shows a decrease in the severity of forest and land fires that occurred in 2021 and 2022.